PENGARUH MEDIA PEMBELAJARAN DAN MOTIVASI TERHADAP HASIL BELAJAR DRIBBLING PASSING DALAM PERMAINAN SEPAKBOLA PADA SISWA SMA NEGERI 1 SEMARANG - Sahabul Adri AR (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2015)
The purpose of this study is to determine: 1) the difference of the effect in using the learning media Audio visual on the result learning on football. 2) The difference of the effects between high motivation and low motivation on the result learning on football. 3). The interaction between learning media and students’ motivation on the learning result of football. This study uses experiment method with a factorial design 2x2. Population of the research was 530 students second, and samples used in this study around 44 students by using purposive sampling, consist 22 students has high motivation and 22 students has low motivation. The results showed. 1) There were the differences between the use visual media with the proof that f – test (4.915)>f table (4.085). 2). the difference between the effect of high motivation and low motivation on learning result in football with the proof F-test (141.360)> from F table (4.085) and 3). there was an interaction between learning media and motivation on learning result on football with the proof F test (6,433) > F table (4.085).